The Values of Character Education in The Novel of Dilan 1990 Written by Pidi Baiq: Sociology Study - Deni Hadiansah; Harmita Sari; Endang Sugianto (Universitas Cokroaminoto Palopo, 2021)
This study describes the value of character education in the novel Dilan 1990 by Pidi Baiq. The study used a sociological literary approach and content analysis techniques through descriptive analysis methods. The main data source is the novel Dilan: Dia is my Dilan Year 1990 (hereinafter written Dilan 1990) by Pidi Baiq. The results of the study can be concluded that the Dilan 1990 novel has a story in accordance with the psychology of adolescents or high school children. Based on the intertwining of the elements, it can be found that the meaning of character education values ​​includes: religious, nationalist, independent, mutual cooperation and integrity. As for based on sociological insights, it is hoped that it can provide an overview of how the model of friendship or adolescent interaction with the conflicts that accompany their lives. Through the characters, readers can get an idea of ​​how to solve life's problems. From a broader view, the novel Dilan 1990 is expected to be a sufficiently effective means of conveying the author's goals to the reader.